Titanium in Dentistry: Historical development, state of the art and future perspectives - Jorge, Juliana Ribeiro Pala [UNESP]; Barão, Valentim Adelino [UNESP]; Delben, Juliana Aparecida [UNESP]; Faverani, Leonardo Perez [UNESP]; Queiroz, Thallita Pereira; Assunção, Wirley Goncalves [UNESP] (Wolters Kluwer, 2013)
Titanium is a metallic element known by several attractive characteristics, such as biocompatibility, excellent corrosion resistance and high mechanical resistance. It is widely used in Dentistry, with high success rates, providing a favorable biological response when in contact with live tissues. Therefore, the objective of this study was to describe the different uses of titanium in Dentistry, reviewing its historical development and discoursing about its state of art and future perspective of its utilization. A search in the MEDLINE/PubMed database was performed using the terms 'titanium', 'dentistry' and 'implants'. The title and abstract of articles were read, and after this first screening 20 articles were selected and their full-texts were downloaded. Additional text books and manual search of reference lists within selected articles were included. Correlated literature showed that titanium is the most used metal in Implantology for manufacturing osseointegrated implants and their systems, with a totally consolidated utilization. Moreover, titanium can be also employed in prosthodontics to obtain frameworks. However, problems related to its machining, casting, welding and ceramic application for dental prosthesis are still limiting its use. In Endodontics, titanium has been used in association to nickel for manufacturing rotatory instruments, providing a higher resistance to deformation. However, although the different possibilities of using titanium in modern Dentistry, its use for prostheses frameworks still needs technological improvements in order to surpass its limitations. © 2012 Indian Prosthodontic Society.
Keywords: Dental materials; Prosthesis; Titanium